"Making it okay": professionals in high-stress environments construct their understanding of the impact of a yoga-based retreat designed to build resilience. Issue 1 (31st December 2022) - Reeves, Tegan J.; Dyer, Natalie L.; Borden, Sara; Dusek, Jeffery A.; Khalsa, Sat Bir Singh
ABSTRACT: Purpose: While there is growing evidence for resilience building programmes, to date research has not explored how professionals construct understanding of programme impact. RISE (resilience, integration, self-awareness, engagement), a 5-day yoga-based retreat programme, has been linked with positive wellness outcomes. This qualitative inquiry explores participants' reflection and experience 3 months after programme completion. Methods: Through a grounded constructivist lens, in-depth semi-structured phone interviews were conducted with 17 adult professionals in high-stress work environments who attended RISE. Initial hand-coding informed codebook development for systematic coding using directed content analysis using sensitizing structuring. Results: Two integrated perceptions woven through five themes. Persistent threads of experiential learning and sense of permission provided structure for themes found. Five interrelated themes related to psychological health and workplace dynamics were (1) use of acquired behavioural skills and practices; (2) lived mindfulness; (3) resilience to stress and emotion regulation (4) self-care and self-compassion, and (5) sharing with others. Conclusion: Findings provide meaningful interpretation of previously reported programme efficacy by contextualizing perceived benefits within participants' constructed understanding of change. Specifically, environmental, social, and experiential considerations have suggested implications for resilience building programmes. Abbreviations: RISE (resilience, integration, self-awareness, engagement)